Combination of paeoniflorin and liquiritin alleviates neuropathic pain by lipid metabolism and calcium signaling coordination - Chen, Yan-Yan; Feng, Li-Mei; Xu, Ding-Qiao; Yue, Shi-Jun; Fu, Rui-Jia; Zhang, Mei-Mei; Tang, Yu-Ping (Frontiers in Pharmacology, 2022)
Neuropathic pain (NP) affects 7%–10% of the general population and is still hard to cure. Here, we validated the therapeutic effect and demonstrated the mechanism of paeoniflorin and liquiritin combination (PL) on NP from the perspective of integrated lipidomics and transcriptomics for the first time. SwissTargetPrediction indicated that PL mainly targets lipid metabolism. Notably, lipidomics revealed that imbalanced lipid levels in the NP model could be reprogrammed to normal levels by PL treatment. RNA-sequencing showed that PL treatment could also rebalance the lipid metabolism in an indirect manner. Pathway analysis highly enriched the calcium signaling pathway among the most significant categories. Altogether, these findings suggested that PL can not only balance the lipid metabolism in direct and indirect manners but also reverse the dysfunctional activation of the calcium signaling pathway, thereby alleviating NP. This helps to better understand the mechanisms of NP and provides a new important potential therapeutic option for NP.